A connectome of the Drosophila central complex reveals network motifs suitable for flexible navigation and context-dependent action selection - Hulse, Brad K; Haberkern, Hannah; Franconville, Romain; Turner-Evans, Daniel; Takemura, Shin-ya; Wolff, Tanya; Noorman, Marcella; Dreher, Marisa; Dan, Chuntao; Parekh, Ruchi; Hermundstad, Ann M; Rubin, Gerald M; et al. (eLife, 2021)
Flexible behaviors over long timescales are thought to engage recurrent neural networks in deep brain regions, which are experimentally challenging to study. In insects, recurrent circuit dynamics in a brain region called the central complex (CX) enable directed locomotion, sleep, and context- and experience-dependent spatial navigation. We describe the first complete electron microscopy-based connectome of the Drosophila CX, including all its neurons and circuits at synaptic resolution. We identified new CX neuron types, novel sensory and motor pathways, and network motifs that likely enable the CX to extract the fly’s head direction, maintain it with attractor dynamics, and combine it with other sensorimotor information to perform vector-based navigational computations. We also identified numerous pathways that may facilitate the selection of CX-driven behavioral patterns by context and internal state. The CX connectome provides a comprehensive blueprint necessary for a detailed understanding of network dynamics underlying sleep, flexible navigation, and state-dependent action selection.